Syntactical interference of Katigan language to Indonesian language in SMP Negeri 1 at Katingan Tengah regency at Central Kalimantan - Irni Cahyani; Lili Agustina (English, 2017)
Syntactical interference of Language of Katingan to Indonesian in Katingan Tengah School at Katingan Tengah regency has been a focus of some language research recently. The research was aimed at recognizing and identifying interference in second language acquisition. The term interference refers to two different linguistic phenomena, namely psychological interference and sociolinguistic interference. Psychological interference refers to the influence of old habits as a result of learning something against something being studied[1]. While sociolinguistic interference refers to the interaction of the language, such as loan or word change. Factors that cause interference is the factor of contact language and language skills. Interference is caused by language contact factors in bilingual societies and an unsteady language mastery factor in second language learners or foreign language learners [2]. This is in accordance with the teacher's opinion that there are still errors in the language, whether it's talking and writing activities. That's what makes researchers interested in doing this. Based on the above problems, it can be identified some points, namely the influence of the first language habit of Katingan in using a second language, Indonesian language, language skills that have not been steady in the second language learning and errors in the language, because of the influence of the first language. The result of research on the syntactic interference aspects of Katingan language to Indonesian language was found in two types of syntactic interference which was contained in oral and written language of students of SMPN 1 Katingan Tengah, such as: (1) Interference phrase to Indonesian language and (2) Interference sentence to Indonesian language.